Professional development during simulation-based learning: experiences and insights of preservice teachers. Issue 1 (1st January 2023) - Levin, Orna; Muchnik-Rozanov, Yulia
ABSTRACT: In this study, we examined the professional development of preservice teachers (PTs) in the framework of simulation-based learning (SBL) during pedagogical courses. The study's goal was to examine the reflective discourse patterns by focusing mainly on the linguistic behaviour of the SBL's participants, to describe their experiences that tended to contribute to the professional development. To this end, two SBL workshops were studied using three data collection tools: (a) workshop transcripts, which were analysed using positioning theory and the systemic functional linguistic method; (b) interviews conducted with the main SBL participant in each workshop; and (c) observations collected by two simulation instructors who viewed the videotaped simulation of the two workshop scenarios. Thus, we obtained a broad picture of PTs' perceptions of the SBL experiences. The data analysis revealed distinctive patterns of behaviour during the participants' discursive interactions, pointing at three directions of PTs' learning process. The findings show that SBL, as perceived by PTs, is a unique and novel tool that contributes to the enrichment of their professional training as well as benefits their professional development. The study contributes to the field by suggesting the connection between SBL experiences of the participants and the professional development process they undergo.